Analysis of Fama and French 3-Factor Model Variables in the Formation of Expected Stock Returns (Issuers of Lq-45 Index Member Stocks for the Period 2020 – 2022) - Harold Kevin Alfredo (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Fama and French Three Factor Model is one of the models for calculating expected return on stock portfolios that can be used by investors. This model was developed by Eugene F. Fama and Kenneth R. French by adding two factors, namely company size (SMB), and company book value (HML) to the CAPM calculation model. The purpose of this study is to determine stock issuers that can provide high expected returns to investors, determine the overall influence and each variable in Fama and French Three Factor Model (market return, SMB, and HML) on the expected return of each portfolio used in this study consisting of 6 portfolios, namely Big High, Big Medium, Big Low, Small High, Small Medium, and Small Low, and to all 6 portfolios in 2020, 2021, and 2022 respectively. This study used 28 selected stock issuers listed on the LQ-45 Index consecutively from 2020 - 2022 using the purposive sampling method from the period 2020 - 2022. The Multiple Linear Regression method is used to determine the level of influence of the whole and each independent variable on the dependent variable. The results show that mining sector issuers are the issuers that provide the highest expected return to investors during the period 2020 - 2022. Based on the results of Linear Regression, there is a significant difference in results, between doing linear regression for each portfolio (Big High, Big Medium, Big Low, Small High, Small Medium, and Small Low) and doing linear regression on portfolios divided by observation year (2020, 2021, and 2022).